2013
DOI: 10.1179/1743294413y.0000000144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pulse waveforms on electrodeposition of Zn coating

Abstract: Zn coatings were electrodeposited successfully from a ChCl based ionic liquid with four different pulse waveforms, namely, square pulse, sine pulse, sawtooth pulse and triangular pulse. The compositions and microstructures of the Zn coatings were investigated by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD). The adhesion and corrosion resistance of the Zn coatings on magnesium alloy was evaluated using scratch tests and electrochemical polarisation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…29 In order to improve the bad deposit morphology, Dai et al have recently investigated the influence of different pulse waveforms on the composition and the microstructure of zinc deposits from choline chloride based deep eutectic solvents. 30 Liu et al studied the electrodeposition of zinc films from two ionic liquids namely 1-butyl-1- BuIm = N-butylimidazole; Tf 2 N -= bis(trifluoromethylsulfonyl)imide), which are suitable as electrolytes for electroplating of zinc at high current densities. In analogy to the traditional dialkylimidazolium ionic liquids, the introduction of two different N-alkylimidazoles, differing only in the alkyl chain length, is expected to result in zinc(II) complexes with lower melting points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In order to improve the bad deposit morphology, Dai et al have recently investigated the influence of different pulse waveforms on the composition and the microstructure of zinc deposits from choline chloride based deep eutectic solvents. 30 Liu et al studied the electrodeposition of zinc films from two ionic liquids namely 1-butyl-1- BuIm = N-butylimidazole; Tf 2 N -= bis(trifluoromethylsulfonyl)imide), which are suitable as electrolytes for electroplating of zinc at high current densities. In analogy to the traditional dialkylimidazolium ionic liquids, the introduction of two different N-alkylimidazoles, differing only in the alkyl chain length, is expected to result in zinc(II) complexes with lower melting points.…”
Section: Introductionmentioning
confidence: 99%
“…29 In order to improve the bad deposit morphology, Dai et al have recently investigated the influence of different pulse waveforms on the composition and the microstructure of zinc deposits from choline chloride based deep eutectic solvents. 30 Liu et al studied the electrodeposition of zinc films from two ionic liquids namely 1-butyl-1methylpyrrolidinium trifluoromethylsulfonate [C 4 mpy][TfO] and 1-ethyl-3-methylimidazolium trifluoromethylsulfonate [C 2 mim][TfO] containing 0.2 M zinc(II) triflate (Zn(TfO) 2 ) on gold electrodes, as a function of water content and deposition temperature. 31 The authors also used the ionic liquid [C 4 mpy]-[TfO]-0.2 M Zn(TfO) 2 to electrodeposit two-and three-dimensional macroporous zinc films in polystyrene templates on gold electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In industry, the deposition of Zn coatings usually relies upon the electrodeposition techniques due to the high efficiency, low cost and easy preparation of nanoparticulate films. Many factors have been reported that affect the surface morphology and texture of the electrodeposited Zn films, such as the temperature, pH value, current density, [3][4][5] concentrations of Zn(II) ions, 6 usage of agents 7 and properties of anions 8,9 because electrodeposition generally involves the following processes: liquid phase mass transfer, pretransformation, charge transfer and electrocrystallisation. It is well known that the organic additives also play very important roles in the electrolytic baths, 10,11 which improve throwing power and solubility of the brighteners in the bath solutions, and thus smoothen and refine the grain size of deposited films.…”
Section: Introductionmentioning
confidence: 99%